2017
DOI: 10.9724/kfcs.2017.33.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Steamed Bread Containing Pomegranate (Punica granatum L.) Peel Powder

Abstract: Purpose: Pomegranate has been reported to exhibit medical properties such as antimicrobial, antimutagenic, anticancer, and anti-inflammatory effects. Especially the pomegranate peel as a by-product of the juice industry possesses more polyphenols with an antioxidant effect than the pomegranate flesh does. This study aimed to investigate the effect of the pomegranate peel on the quality characteristics of steamed bread. Methods: Steamed bread containing pomegranate peel was prepared with 0%, 1%, 3%, 5%, and 7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These physiological activities are generally considered to be related to the reducing properties, free radical scavenging ability and anti‐lipid peroxidation properties of pomegranate polyphenols. Several studies have introduced pomegranate peel powder into the production of steamed bread to improve the antioxidant capacity 22 . The application of pomegranate fruit powder (PFP) in yogurt promoted the formation of dense microstructure, and improved the antioxidant capacity, in vitro bioavailability and storage stability of yogurt 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These physiological activities are generally considered to be related to the reducing properties, free radical scavenging ability and anti‐lipid peroxidation properties of pomegranate polyphenols. Several studies have introduced pomegranate peel powder into the production of steamed bread to improve the antioxidant capacity 22 . The application of pomegranate fruit powder (PFP) in yogurt promoted the formation of dense microstructure, and improved the antioxidant capacity, in vitro bioavailability and storage stability of yogurt 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have introduced pomegranate peel powder into the production of steamed bread to improve the antioxidant capacity. 22 The application of pomegranate fruit powder (PFP) in yogurt promoted the formation of dense microstructure, and improved the antioxidant capacity, in vitro bioavailability and storage stability of yogurt. 23 Besides, studies have shown that pomegranate juice served with bread reduced postprandial blood sugar.…”
Section: Introductionmentioning
confidence: 99%